Peculiarities of Emotional Sphere Development of Primary School Pupils - Viktor Rybalko; Vira Kalenska (Pedagogical Discourse, 2012)
The article is dedicated to the emotional sphere as particular category of psychical processes and state of personality. Structure and peculiarity of development of emotional sphere at the primary school age is examined. Recommendations about development of emotional sphere of personality for teachers and psychologists are suggested.